Physicochemical Properties and Phase Behavior of Didecyldimethylammonium Chloride/Alkyl Polyglycoside Surfactant Mixtures. Issue 4 (24th March 2015) - Han, Zhiguo; Yang, Xiuquan; Liu, Yong; Wang, Jiajia; Gao, Yuyang
Abstract: Mixed surfactant systems, used in many formulations, have aroused great attention and interest from researchers and industry due to the possibility of synergism. Alkyl polyglycoside (APG) and didecyldimethylammonium chloride (DDAC) mixtures combine the excellent properties of pure surfactants and play an important role in the development of multi‐functional washing products. To study the synergism between APG and DDAC, the physicochemical properties of different mixed systems have been investigated. The critical micelle concentration (CMC) is about 180 mg·L −1 and the surface tension at the CMC is about 26.0 mN·m −1 at a mass fraction of 40 % DDAC (ωDDAC 40 %). The values are significantly lower than pure surfactants. The foaming property shows the best performance at ωDDAC 20 %. When the mass fraction of DDAC is 80 %, the mixture exhibits better wetting and emulsifying properties. Synergism was observed in surface tension, foaming and emulsifying properties, while the wetting ability and detergency exhibited no such effects. Phase behavior of the APG/DDAC/water ternary system has also been carried out by polarized optical microscope. The phase diagram is characterized by a micellar phase, a region where lamellar and micellar phases coexist and a lamellar phase.